Water information networks: infrastructure for efficient management of water - Mareels, Iven, author; Ooi, Su Ki, author; Thoms, Gavin, author; Skafidas, Stan, author; Oakes, Tony, author; Langford, John, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
In collaboration with many stakeholders, NICTA, Australia's national information and communications research centre, conducts research in the area of Water Information Networks (WIN). In this project NICTA develops information infrastructure solutions in support of efficient water (distribution) management. Researchers in WIN, in collaboration with Rubicon Systems Australia Pty Ltd (Rubicon) developed the idea of Total Channel Control™ (TCC™) which is patented and commercialized through Rubicon. TCC™ automates the water distribution management of large scale open canal irrigation networks with the express purpose of achieving greater efficiency. It realizes near on-demand response of gravity fed water distribution networks. As testified by a recent audit of a commercial implementation of TCC™ in the Coleambally irrigation district in New South Wales, Australia, a water distribution efficiency of 90% can be realized. Moreover gains in on-farm efficiency are simultaneously achieved due to the near "on-demand" delivery of water which allows irrigators to significantly modify their irrigation schedules, so as to better suit their local requirements. At present, WIN researchers in collaboration with the Melbourne based UniWater research centre are considering the joint automation of on-farm irrigation and distribution canals. The goal is to realize that for every drop of water "requested" by the plants in the field, a drop of water is delivered through the distribution network from "reservoir-to-the-plant". The information infrastructure required for such a scheme is discussed.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.